Berkeley archaeology : the Archaeological Research Facility newsletter - University of California Berkeley - Archaeological Research Facility (1993)
"From their headquarters at the Jewish Central Information Office (JCIO), Alfred Wiener and his colleagues used their unrivalled network of contacts to collect over 350 eyewitness accounts describing the events of 9 and 10 November 1938 in cities, towns and villages throughout Germany and Austria." [self-description]